2018
DOI: 10.4995/raet.2018.11106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación del uso de LiDAR discreto, full-waveform y TLS en la clasificación por composición de especies en bosques mediterráneos

Abstract: <p>LiDAR technology –airborne and terrestrial- is becoming more relevant in the development of forest inventories, which are crucial to better understand and manage forest ecosystems. In this study, we assessed a classification of species composition in a Mediterranean forest following the C4.5 decision tree. Different data sets from airborne laser scanner full-waveform (ALS<sub>FW</sub>), discrete (ALS<sub>D</sub>) and terrestrial laser scanner (TLS) were combined as input data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Some successful studies have been done using aerial and terrestrial laser scanning point clouds to classify forest species composition (Torralba et al, 2018). However, the frequency of application of these techniques is limited by their cost.…”
Section: Introductionmentioning
confidence: 99%
“…Some successful studies have been done using aerial and terrestrial laser scanning point clouds to classify forest species composition (Torralba et al, 2018). However, the frequency of application of these techniques is limited by their cost.…”
Section: Introductionmentioning
confidence: 99%
“…These studies generally show that CH estimations are more accurate using ALS than TLS (Hilker et al, 2010), while characterization of the foliage profile is estimated with more accuracy by TLS, especially in the lower strata (Chasmer et al, 2006;Hilker et al, 2010), where understory vegetation is found. On the other hand, other studies concur on a more accurate estimation of forest structural attributes (Anderson et al, 2016), AGB (Nie et al, 2017), stand volume (Lindberg et al, 2012), and the classification of species composition (Torralba et al, 2018).…”
Section: Introductionmentioning
confidence: 88%
“…For applications in forested environments, the useful portion of the TLS point cloud extent is often limited (10 -30 m) with a hemispherical view around the sensor. Withstanding that, many studies have demonstrated the capabilities of TLS to estimate and extract forest stand attributes (Watt and Donoghue, 2005;Moskal and Zheng, 2011;Kankare et al, 2013;Srinivasan et al, 2015;Liang et al, 2016;Ravaglia et al, 2019), and fewer on the classification of tree species (Othmani et al, 2013;Lin and Herold, 2016;Torralba et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations